Design and key technology analysis of buoy-type aviation homing depth charge - YE Licong, ZHAO Shendong, ZHANG Feifei (Zhihui kongzhi yu fangzhen)
In order to solve the problems such as low hit rate, difficult evaluation of underwater combat effectiveness and single working mode of the aviation homing depth charge in combat and training, this paper proposes a design of a buoy-type aviation homing depth charge which adds floating air bag, release cable, radio transmitting and receiving device to the structure of the ordinary aviation homing depth charge. It’s helpful to improve the submarine search probability of depth charge, increase efficiency evaluation means, flexible control working mode, and efficient handling of special situation, etc. This paper also introduces its structure and work flow, four key technologies such as surface floating technology, data transmission technology, data cable technology, remote control technology, are analyzed, and its application prospects are prospected, which can provide reference for the development of aviation homing depth charge.